Bimetallic ordered mesoporous carbon from lignin for catalytic selective hydrogenation of levulinic acid to γ-valerolactone. (1st June 2023) - Wang, Xiaoqi; Qi, Xinhua; Qiu, Mo; Shen, Feng; Yang, Jirui; Shen, Boxiong
Graphical abstract: Highlights: Bimetallic OMC was fabricated with lignin and Ni 2+ followed by impregnated with Ru. Ni/Ru@WOMC exhibited superior activity for LA hydrogenation under mild conditions. High GVL yield of 100 % was obtained under mild conditions (80 °C or 0 MPa H2 ). Ni/Ru@WOMC was applicable for high initial LA loading with high GVL yield. Abstract: Herein, a Ni/Ru bimetallic ordered mesoporous carbon (Ni/Ru@WOMC) was prepared through solvent evaporation induced self-assembly (EISA) method with walnut shell organosolv lignin as carbon precursor and Ni 2+ as crosslinking agent followed by impregnating small amount of Ru, where the mass ratio of Ni/Ru was about 10:1. The resulting material showed superior catalytic activity on hydrogenation of levulinic acid (LA) to γ-valerolactone (GVL). A nearly 100 % GVL yield could be obtained in 2-propanol solvent under mild conditions at a low reaction temperature of 80 °C in 4 h reaction time. The Ni/Ru@WOMC catalyst could be used at least 5 times without obvious loss of its catalytic performance, which can be ascribed to the confinement effect provided by their ordered mesoporous structure. This successful development of Ni/Ru@WOMC in the hydrogenation of LA to GVL opens up new opportunities for the catalytic application of lignin derived functionalized ordered mesoporous carbon in biomass transformation reactions.